Pelatihan Konseling Realitas Berbasis Tolong Diri Digital Bermuatan Ajaran Ki Hadjar Dewantara pada Guru BK SMP - Nur Mega Aris Saputra; Muslihati Muslihati; M. Ramli; Ahmad Yusuf Sobri; Muhammad Rafli; Muh. Nur Alamsyah (AJAD : Jurnal Pengabdian kepada Masyarakat, 2025)
The problems of junior high school students are getting more and more varied because information is easy to get. This condition makes it hard for guidance and counseling teachers to give the best help with the current limits. Also, since students live with the digital world, guidance and counseling services must change too. So, this training program aims to improve the skills of junior high school guidance and counseling teachers in Malang Regency. The program used a project-based learning model through six steps: design, preparation, introduction, core training, closure, and reporting. There were 20 guidance and counseling teachers from the Junior High School Guidance and Counseling Teachers Association of Malang Regency as participants. The results showed that there was a significant increase in teachers’ competencies with a significance value of p = 0.000 (p < 0.05). These results proved that the self-help approach integrated with reality counseling based on the values of Ki Hadjar Dewantara could improve the competence of guidance and counseling teachers in providing autonomous and local-based counseling services to introduce a new counseling paradigm that encourages student independence in the digital era.